Strategi Pasangan “Sadia” dalam Memobilisasi Pemilih melalui Guraklih pada PILKADA Kabupaten Bangli Tahun 2020 - Arimbawa, I Ketut Wiratama; Noak, Piers Andreas; Puspitasari, Ni Wayan Radita Novi (Jurnal Nawala Politika, 2023)
This study aims to explore the strategy of the SADIA pair in mobilizing voters through guraklih at the 2020 Bangli district election. Furthermore, this research is framed using the theory of Political Strategy from Peter Schroder. The results of this study are: guraklih is a voter mobilization team made by the Indonesian Democratic Party of Struggle (Partai Demokrasi Indonesia Perjuangan, PDI-P). This guraklih succeeded in moving voters around 30% of the total votes for the SADIA pair in the 2020 Bangli Regency Pilkada and there were also factors that influenced the formation of guraklih in Bangli Regency such as the lack of public interest in going to TPS, bad weather during the regional elections, and some geographical difficulties in Bangli Regency such as the number of highlands existed. Keywords: Political Strategy, Guraklih, Voter Mobilization, Pilkada 2020